Indonesia Economic Prospects, December 2020 : Towards a Secure and Fast Recovery - World Bank (World Bank, Washington, DC, 2020)
The Indonesian economy is slowly recovering following the partial reopening of the domestic and global economies. But the pace of recovery is uneven across sectors. Several labor market indicators are significantly weaker than before the crisis. The monetary response to the crisis has been strong but involves macro-financial risks that need to be managed. The fiscal response to save lives and livelihoods and stimulate the recovery has been decisive. Albeit relatively low compared to peer countries, public debt is rising, and the fiscal space risks tightening in the absence of reforms. Notwithstanding the policy response, the current pace of recovery indicates that Indonesia will finish this year in recession, the first time in two decades.